Development of Press Die for Aluminum Open - Type Scaffolding Board - Sajjad, Muhammad; Won Jung, Dong (International Journal of Engineering and Technology, 2019)
Scaffolding as part of the temporary facilities category in construction has significant impact on construction sites must be thoroughly designed, manufactured, procured and managed. As part of the basic industry, the vessel plate is essential when working on a high level e.g. construction of the buildings or ships, can be regarded as an important. In order to increase the main performance and production volume of the footrest plates, the new open type aluminum ranch was developed through this research study and in which the production process line of the footrest plates was improved. The main contents of the research task is production of holes in aluminum plate which is drastically reduced from 10 to 5 process, thus increases production rate and a heavy reduction in production time and burden for the worker. By using aluminum instead of the existing iron material used in the iron sheets, makes lighter and easy to handle. Reviewing the choice of aluminum materials is verified through structural analysis to reduce product development costs, which can save time and shortening the press process. Initially FEM (Finite Element Method) were used for technical performance and Simultaneous processing of holes separated from the top and bottom plates, and structural analysis of new material (aluminum). As a result of our research study we lightening the weight of Scaffolding Board which causes reduction of shift time and work by increasing the working efficiency of workers. It also gives a positive impact on performance through such effects as easy to handle by workers and also effective to different environment conditions.Â Â Â